2004
DOI: 10.1111/j.1369-7625.2004.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

How is patient‐centred care understood by the clinical, managerial and lay stakeholders responsible for promoting this agenda?

Abstract: Aims and objectives This study explores how the term patient-centred care is understood, particularly by those who are involved in translating the concept from a theoretical idea into a practical application. It examines the ways in which intermediate level stakeholders such as health service managers, educationalists, professional leaders and officers of patient bodies understand and promote patient-centred care among health professionals actually delivering patient care.Design Qualitative interview study.Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 5 publications
4
87
0
Order By: Relevance
“…We know that, when asked directly, clinicians tend to espouse patient-centeredness and believe that they themselves engage in patient-centred care, within the bounds of various professional constraints and organisational, personal and patient-derived limitations such as lack of resources and leadership, lack of skill and time, and difficulties in communicating with certain groups of patients (Tufano, Ralston et al 2008). There is, however, some empirical evidence that health professionals defining patient-centred care actually adopt a model in which professional priorities determine patients' needs (Gillespie, Florin et al 2004) and that adopting a patient-centred ideology can threaten clinicians' sense of status in relation to patients and colleagues (O'Flynn and Britten 2006). While this research is helpful, it is limited because doctors' espoused stance towards patient-centred care, whether positive or negative, might not accord with their actual (personal and cultural) values.…”
Section: Background and Rationalementioning
confidence: 99%
“…We know that, when asked directly, clinicians tend to espouse patient-centeredness and believe that they themselves engage in patient-centred care, within the bounds of various professional constraints and organisational, personal and patient-derived limitations such as lack of resources and leadership, lack of skill and time, and difficulties in communicating with certain groups of patients (Tufano, Ralston et al 2008). There is, however, some empirical evidence that health professionals defining patient-centred care actually adopt a model in which professional priorities determine patients' needs (Gillespie, Florin et al 2004) and that adopting a patient-centred ideology can threaten clinicians' sense of status in relation to patients and colleagues (O'Flynn and Britten 2006). While this research is helpful, it is limited because doctors' espoused stance towards patient-centred care, whether positive or negative, might not accord with their actual (personal and cultural) values.…”
Section: Background and Rationalementioning
confidence: 99%
“…The overall purpose of this study was to describe nurse practitioners' self-reported implementation of PCC. Although PCC is considered an essential element of high quality care and several studies and reviews of literature have been conducted to clarify what exactly comprises PCC [7][8][9][10][11][12][13][14][15], there is no agreement on its conceptualization [16]. Differences in the definition of what constitutes PCC lead to variability in its operationalization.…”
Section: Introductionmentioning
confidence: 99%
“…This apparent resistance has been understood as stemming from "old-fashioned," paternalistic, clinical values (Gillespie, Florin, and Gillam 2004); from concerns about the resources required to, for example, spend more time talking to patients (Tufano, Ralston, and Martin 2008); from the perception that adopting a patientcentred ideology can threaten clinicians' sense of status in relation to patients and colleagues (O'Flynn and Britten 2006); and even from "cynical disengagement" on the part of students and doctors (Coulehan and Williams 2003;White et al 2009). We would argue that doctors' apparent resistance to patient-centred care, and other similar humanistic medical movements, might stem in part from a the perception that such movements are already consistent with current medical values and practice and that their formalisation into social movements, with the associated bureaucratic criticisms and demands, are yet another sign of managerial disrespect.…”
Section: The Effects Of Perceived Disrespectmentioning
confidence: 99%